2022
DOI: 10.1177/00031348221103648
|View full text |Cite
|
Sign up to set email alerts
|

A Surgeon’s Guide to Artificial Intelligence-Driven Predictive Models

Abstract: Artificial intelligence (AI) focuses on processing and interpreting complex information as well as identifying relationships and patterns among complex data. Artificial intelligence- and machine learning (ML)-driven predictions have shown promising potential in influencing real-time decisions and improving surgical outcomes by facilitating screening, diagnosis, risk assessment, preoperative planning, and shared decision-making. Fundamental understanding of the algorithms, as well as their development and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…However, the primary advantage of AI lies in empowering anesthesiologists to adopt a proactive approach to address clinical issues. For example, AI has been used for presurgical evaluation [11][12][13], to predict patient responses to anesthesia [14], to automate drug dosing [15], to monitor patients during surgery [6], and other purposes [16][17][18][19][20][21][22][23][24][25][26][27] (Table 1). Pain Management AI can help adjust the dosage and administering of drugs to achieve optimal postoperative pain control.…”
Section: Ai In Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the primary advantage of AI lies in empowering anesthesiologists to adopt a proactive approach to address clinical issues. For example, AI has been used for presurgical evaluation [11][12][13], to predict patient responses to anesthesia [14], to automate drug dosing [15], to monitor patients during surgery [6], and other purposes [16][17][18][19][20][21][22][23][24][25][26][27] (Table 1). Pain Management AI can help adjust the dosage and administering of drugs to achieve optimal postoperative pain control.…”
Section: Ai In Anesthesiamentioning
confidence: 99%
“…[8] Research and Analysis AI can help analyze vast amounts of data from anesthesia records, patient charts, and other sources to identify patterns, trends, and insights that could help improve patient outcomes and safety. [26,27] Although with limitations due to classification difficulties, the applications of AI in anesthesia can be schematically summarized into Clinical Decision Support System (CDSS) applications and pharmacological and mechanical robotic systems. Furthermore, teleanesthesia includes strategies of telemedicine (preoperative assessment and post-operative monitoring), as well as device networking for improving logistics in the operating room and augmented reality approaches for training and assistance (Figure 1).…”
Section: Ai In Anesthesiamentioning
confidence: 99%
“…Hernigou and Scarlat suggested that ChatGPT could be a valuable asset in orthopedics. They explored various roles for ChatGPT, such as acting as author, reviewer, publisher, and editor, and its potential to address numerous questions related to the technology [49]. LLMs are used in ChatGPT, a general‐domain AI model that has attracted considerable interest.…”
Section: Applications Of Chatgpt In Orthopedicsmentioning
confidence: 99%
“…6ChatGPT Assists orthopedic practitioners by providing rapid access to large amounts of medical information, research papers, and accurate treatment guidelines. Additionally, it supports clinicians in making correct diagnoses, choosing suitable treatment options, and developing personalized care plans for patientsResearch[49] 7 ChatGPT Provides support for queries related to total knee arthroplasty and total hip arthroplasty by question type and topic to provide credible information Surgery[50] 8LLMs and ChatGPT Used to investigate the orthopedic surgery board examination (American Board) by challenging performance and knowledge that are equivalent to that of a firstyear orthopedic surgery resident Education[51] …”
mentioning
confidence: 99%
“…9-13 A detailed overview of the algorithms, model development, performance metrics, and interpretation is previously published by our research group. 14…”
Section: Modeling Techniquesmentioning
confidence: 99%